2021
DOI: 10.24251/hicss.2021.805
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Implementation of AI in Organizations: Findings from a Delphi Study

Abstract: Artificial intelligence (AI), like many technological innovations before it, promises to revolutionize organizations. However, implementing AI in organizations is not as simple as it may appear. This exploratory research aims to unearth barriers to the implementation of AI in organizations. The methodology is based on a ranked-order Delphi study with 18 AI experts. By comparing our results with previous research on barriers to implementation of other information systems and to conceptual and practitioner liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 31 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Extant research on the challenges of adopting AI for public service delivery has pointed to barriers related to AI-specific capabilities, including capabilities for managing algorithmic performance and data governance, more general technical and managerial capabilities, and regulatory hurdles (Sun and Medaglia, 2019;Wirtz et al, 2019;Mikalef et al, 2022). These barriers rhyme with the ones identified for AI adoption by organizations beyond the public sector (Bérubé et al, 2021). Schmager (2022) found that existing approaches cannot be directly translated to the public sector context and need to be adapted and individually scrutinized.…”
Section: Ai In Public Service Deliverymentioning
confidence: 99%
“…Extant research on the challenges of adopting AI for public service delivery has pointed to barriers related to AI-specific capabilities, including capabilities for managing algorithmic performance and data governance, more general technical and managerial capabilities, and regulatory hurdles (Sun and Medaglia, 2019;Wirtz et al, 2019;Mikalef et al, 2022). These barriers rhyme with the ones identified for AI adoption by organizations beyond the public sector (Bérubé et al, 2021). Schmager (2022) found that existing approaches cannot be directly translated to the public sector context and need to be adapted and individually scrutinized.…”
Section: Ai In Public Service Deliverymentioning
confidence: 99%
“…Although AI systems can bring many benefits to the workplace, it is important to recognise that their use does not always and automatically lead to a systematic improvement in employees' skills. According to the literature (Alsheibani et al, 2019;Bérubé et al, 2021;Nylin et al, 2022), if not properly managed, the use of AI in the workplace and the related organisational changes may improve or increase employees' skills while limiting the pace of work and reduce employees' autonomy. Indeed, increased complexity and more need for interaction and adaptability are introduced when AI is introduced.…”
Section: 2020)mentioning
confidence: 99%
“…Although opportunities for AI in the public sector are exciting, it is not used as much by the government as by the private sector (Bailey and Barley, 2020), and research on the AI-backed public service delivery is few and far between (Kankanhalli et al , 2019). This is because AI is a complicated field with a steep learning curve, and the government has a unique purpose and environment that makes it hard to use (Bérubé et al , 2021; Mahmoud et al , 2020). The notion that AI will increasingly match or exceed human performance in terms of the work roles implies that there shall be a radical transformation of the operational edifices of the public sector, thereby disrupting the conventional public administration practices (Agrawal Gans and Goldfarb, 2017; Füller et al , 2022).…”
Section: Basic Conceptsmentioning
confidence: 99%